Electroimmunochemical Characterization of Endothelial Cell Proteins: Antigenic Relationship with Platelet and Erythrocyte Membrane Proteins - Børsum, Tone; Hagen, Inger; Bjerrum, Ole J (Thrombosis and Haemostasis, 1987)
Human endothelial cells isolated from umbilical cords and cultured in primary cultures were solubilized in Triton X-100 and examined by crossed immunoelectrophoresis using rabbit antiserum against endothelial cells. Endogeneous labelling of the endothelial cell proteins with 35S-methionine or 14C-mannose followed by crossed immunoelectrophoresis and autoradiography revealed about 30 or 8 immunoprecipitates, respectively. Antigenic relationship between endothelial cell proteins and proteins in human platelets or erythrocyte membranes was demonstrated by use of the corresponding antisera and by antigen addition experiments. One of the endothelial cell proteins cross-reacted with antiserum against erythrocyte membranes and showed a partial antigenic identity reaction with the band 3 protein complex of erythrocyte membranes. The same protein showed antigenic relationship also with a platelet protein. In addition, endothelial cells contain at least 7 proteins antigenically related to platelet proteins, of which at least 5 were labelled with 14C-mannose and thus were glycoproteins. Three of these glycoproteins were antigenically related to proteins from isolated platelet membranes and three were related to the release products obtained after thrombin treatment of platelets. The present study demonstrated numerous platelet and endothelial cell proteins that were antigenically related, more than previously anticipated.
Keywords: Blood platelets; Endothelium; Erythrocyte membrane; Immunoelectrophoresis; Proteins